2006
DOI: 10.1515/hf.2006.045
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional stability of MDF panels produced from heat-treated fibres

Abstract: The objectives of this study were to improve the dimensional stability of medium-density fibreboard (MDF) by heat treatment and to determine the effects of the treatment on the mechanical properties and vertical density profile of the panels. MDF panels were produced from untreated fibres and fibres treated at two different temperatures (150 and 1808C) for 15, 30 and 60 min. Panels produced from heat-treated fibres showed an important reduction in thickness swelling and water absorption after water soaking. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Another work (Mohebby et al 2008) found similar results: water absorption of MDF manufactured with wet thermal pretreated wood was not affected, thickness stability was improved, and mechanical properties were reduced. Garcia et al (2006) showed also reduction of thickness swelling and water absorption of MDF after water soaking. The authors showed that the springback of panels after repeated cycles of adsorption and desorption do not change after thermal pretreatment of wood.…”
Section: Effect Of Wood Thermal Pretreatment On Waferboardmentioning
confidence: 86%
“…Another work (Mohebby et al 2008) found similar results: water absorption of MDF manufactured with wet thermal pretreated wood was not affected, thickness stability was improved, and mechanical properties were reduced. Garcia et al (2006) showed also reduction of thickness swelling and water absorption of MDF after water soaking. The authors showed that the springback of panels after repeated cycles of adsorption and desorption do not change after thermal pretreatment of wood.…”
Section: Effect Of Wood Thermal Pretreatment On Waferboardmentioning
confidence: 86%
“…Changes caused by heat treatment in chemical composition and physical properties (with dimensional stability in focus) were intensely investigated (Repellin and Guyonnet 2005;Esteves et al 2008a;Tuong and Li 2011). Even the dimensional stability of MDF panels can be improved when the fibers are heat-treated (Garcia et al 2006). The surface composition was investigated by modern analytical instruments, such as XPS and ToF-SIMS by Bryne et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…This may also be explained by removal of the hemicellulose component during the latter process with the concomitant increase in the relative lignin content Garcia et al, 2006).…”
Section: Analyses Of Residual Wood Components Following Growth Of P mentioning
confidence: 99%